L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.